2017
DOI: 10.1038/s41598-017-14867-y
|View full text |Cite
|
Sign up to set email alerts
|

Lasting deficit in inhibitory control with mild traumatic brain injury

Abstract: Being able to focus on a complex task and inhibit unwanted actions or interfering information (i.e., inhibitory control) are essential human cognitive abilities. However, it remains unknown the extent to which mild traumatic brain injury (mTBI) may impact these critical functions. In this study, seventeen patients and age-matched healthy controls (HC) performed a variant of the Stroop task and attention-demanding 4-choice response tasks (4CRT) with identical stimuli but two contexts: one required only routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 58 publications
(66 reference statements)
1
8
0
Order By: Relevance
“…These results suggest the presence of a response inhibition deficit following mTBI. Fischer et al (2013) confirmed the reverse brain activation pattern observed by Xu et al (2017) when studying chronic, mild-to-moderate TBI; these authors identified bilateral BOLD signal increases in the caudate nuclei and in the left superior temporal, inferior temporal and cerebellar cortices, especially in relation to failures to inhibit a response.…”
Section: Executive Functionsupporting
confidence: 59%
See 2 more Smart Citations
“…These results suggest the presence of a response inhibition deficit following mTBI. Fischer et al (2013) confirmed the reverse brain activation pattern observed by Xu et al (2017) when studying chronic, mild-to-moderate TBI; these authors identified bilateral BOLD signal increases in the caudate nuclei and in the left superior temporal, inferior temporal and cerebellar cortices, especially in relation to failures to inhibit a response.…”
Section: Executive Functionsupporting
confidence: 59%
“…Impairment of response inhibition has been noted acutely, up to ∼2.3 years after mTBI and up to ∼5.7 years after TBIs of mixed severity ( Dimoska-Di Marco et al, 2011 ; Xu et al, 2017 ), no distinction being drawn between complicated and uncomplicated mTBI. Nevertheless, a large meta-analysis of 41 studies found no relationship between inhibition performance and TBI severity ( Dimoska-Di Marco et al, 2011 ).…”
Section: Executive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown frequently that dual-task performance is more sensitive to change than single task in patients with previous concussion. 26,27 This long term, specifically dual-task deficit may suggest that impaired inhibitory control and/or attentional resources last longer than changes in simple sensory processing, which may explain our acutely concussed sample's differences in both simple visual and dual-task visual reaction time.…”
Section: Concussed Vs Non-concussed Performancementioning
confidence: 91%
“…Reaction time (RT) was used. This test was chosen because it is less affected by mild traumatic brain injury [28].…”
Section: Methodsmentioning
confidence: 99%